2015
DOI: 10.17795/ijcp-3842
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma in Iran: Clinico-Pathological and Treatment-Related Factors Influencing Survival

Abstract: Background:Evidences about survival of the patients with head and neck squamous cell carsinoma (HNSCC) have been scant in our region.Objectives:The aim of current study was to determine clinico-pathological and treatment-related factors, influencing outcome of these patients.Patients and Methods:We have reviewed all patients with a new diagnosis of HNSCC admitted between 2008 and 2014 in “Jorjani Cancer Center”, Tehran, Iran. Overall survival (OS) and event free survival (EFS) of the patients, and their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
4
2
0
Order By: Relevance
“…In current study, all of the patients are men. We found patients with total laryngectomy, poor differentiation, T3-T4 stage, N1-N2 stage, III-IV TNM stage had a worse prognostic survival and these findings are consistent with results of most other studies 11-14 . We also showed that the polymorphisms of rs11903757 near NABP1 gene and rs966423 in DIRC3 gene correlate with prognostic survival in patients with SLCC.…”
Section: Discussionsupporting
confidence: 92%
“…In current study, all of the patients are men. We found patients with total laryngectomy, poor differentiation, T3-T4 stage, N1-N2 stage, III-IV TNM stage had a worse prognostic survival and these findings are consistent with results of most other studies 11-14 . We also showed that the polymorphisms of rs11903757 near NABP1 gene and rs966423 in DIRC3 gene correlate with prognostic survival in patients with SLCC.…”
Section: Discussionsupporting
confidence: 92%
“…All patients in the current study were men. Consistent with other studies, we found that patients with total laryngectomy, poor differentiation, T3–T4 stage, N1–N2 stage or III–IV TNM stage had reduced survival [ 9 12 ]. We developed multivariate Cox regression analysis models that adjusted for the most important covariates, including SNP, tumor differentiation, neck dissection, T stage and TNM stage.…”
Section: Discussionsupporting
confidence: 91%
“…In some researches indicated that patients T-stage and N-stage had demonstrated to be significantly associated with survival and these findings are consistent with results of most other studies. Our study also obtained the consistent conclusion [ 9 , 13 , 14 ]. A multivariate analysis was conducted, taking the variables found to be significant in univariate analyses ( p ≤0.2) into account.…”
Section: Discussionsupporting
confidence: 90%
“…Also the results of other studies are consistent with the present study (6,17,18,(20)(21)(22)(23). One possible explanation for the higher incidence of oral cancer in men can be higher consumption of tobacco and alcoholic products.…”
Section: Sexsupporting
confidence: 92%